Analisis Kondisi Lingkungan Rumah Dengan Kejadian Tuberkulosis Paru di Wilayah Kerja Puskesmas Betung Kabupaten OKU Timur Tahun 2022 - Monita Septidwina; Hamyatri Rawalillah; Santi Rosalina; Nani Sari Murni (LPPM ITEKES Mahardika, 2022)
Pulmonary Tuberculosis is still an infectious disease that is the top killer in the world. Betung Primary Health Center, East Ogan Komering Ulu (OKU) Regency, South Sumatra Province has 31 cases of Pulmonary Tuberculosis (TB) in 2021. This study aims to determine the correlation between home environmental conditions and the incidence of pulmonary TB in the working area of ​​Betung Health Center, East OKU Regency. The research was conducted on April 25 to June 25 2022. The research design used case control. The sample in this study were all patients with pulmonary TB, namely 31 respondents as cases, and 32 respondents as controls. Statistical test using chi square test. The results showed that there was a correlation between lighting (p-value 0.004), ventilation (p-value 0.000) and floor type (p-value 0.022) with the incidence of pulmonary TB, but there was no relationship between residential density and the incidence of pulmonary TB (p-value 0.068). The conclusion in this study is that there is a correlation between lighting, ventilation, type of floor with the incidence of pulmonary tuberculosis, but there is no relationship between residential density and the incidence of pulmonary tuberculosis. Based on the conclusions, the researchers suggest that patients with pulmonary TB should pay more attention to the health of the home environment so that they are in a healthy home environment and minimize transmission and accelerate the healing of patients.